(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
I believe that digital public education is not an omnipotent panacea, however, it is rather desirable and an aim to be achieved. A new pedagogical road, which has many benefits, but equally has a lot of (new) potholes. For me, the (radical) constructivism offered reasonable explanations for these. My writing aims to illustrate the key features of its approach in the light of my experience, as well as the interaction and relationship I have seen with the public education towards digitization. My aim is to make the area more relevant and familiar with images, stories and analogies. I close my writing by presenting my connected research on the topic which was supported by the ÚNKP-17-1 New National Excellence Program of the Ministry of Human Capacities.